Serious Nonsense : Groundhog Lodges, Versammlinge, and Pennsylvania German Heritage - Donner, William Wilkinson (Book collections on Project MUSE., 2016)
"Explores Pennsylvania German versammlinge (meetings), where participants celebrate and preserve their heritage and culture. Argues that these gatherings, conducted in the Pennsylvania German Deitsch language, are rooted in American communicative styles that date back to the late nineteenth and early twentieth centuries, before mass and electronic media"--Provided by publisher.